The human face of biobank networks for translational research - Meir, K.; Gaffney, E.; Simeon-Dubach, D.; Ravid, R.; Watson, P.; Schacter, B.; Morente, M.; Bjugn, R.; Clark, B.; De Blasio, P.; Carpenter, J.; Deschenes, M.; et al. (2011)
The biobanking literature frequently addresses donor and societal issues surrounding biobanking, but the biobanker's perspective is rarely highlighted. While not comprehensive, this article offers an overview of the human aspects of biobanking from the viewpoint of biobank personnel-from biobank formation, through the process, and in addressing post-biobanking issues. As every biobank and biobank network may differ, such factors may vary. Before biobanking can commence, the purpose of the biobank network must be defined, and buy-in achieved from many stakeholders. An attitude of trust and sharing is essential, as is good communication. Developing a biobank is time consuming and laborious. Forming a network requires significantly more time due to the need for cross-institutional harmonization of policies, procedures, information technology considerations, and ethics. Circumstances may dictate whether development occurs top-down and/or bottom-up, as well as whether network management may be independent or by personnel from participating biobanks. Funding tends to be a prominent issue for biobanks and networks alike. In particular, networks function optimally with some level of government support, particularly for personnel. Quality biospecimen collection involves meticulously documented coordination with a network of medical and nursing staff.Examining and sampling operative specimens requires timely collaboration between the surgical and pathology teams. "Catch rates" for samples may be difficult to predict and may occur at a frequency less than anticipated due to factors related to the institution, staff, or specimen. These factors may affect specimen quality, and have a downstream effect on competition for specimens for research. Thus, release of samples requires a fair, carefully constructed sample access policy, usually incorporating an incentive for researchers, and an encouragement to form collaborations. Finally, the public and patient groups should aim to understand the benefits of a biobank network, so that patient care is improved through coordinated biobanking activity.